THE SPECIAL PROJECT REVERSE ENGINEERING STUDY OF RADIOELECTRONIC PRODUCTS - M. S. Kostin; D. S. Vorunichev (Российский технологический журнал, 2017)
With the constant dynamics of the complicated development of the designs of radio electronic products, the development of the ECB, the material and technical and production base of modern radioelectronic facilities, the previously applied reverse engineering methods and technologists become ineffective, and therefore knowledge of them can not fully form the New Implementation Strategy Reverse reaction. While the study and analysis of modern methods and means of prototyping of the Defense industrial complex. In this work, methods and means of special design reverse engineering of the topology of multi-layer printed circuit boards and case integrated circuits are considered. The concept of reengineering repair of radioelectronic equipment in security and video sur-veillance is formulated. The presented basic technological processes of reverse engineering of the circuit configuration of printed-film radio electronic products based on various physical principles of destructive and non-destructive special design research: machining and chemical etching, optical scanning, radio vision, X-ray analysis. For the first time, a method of thermal imaging (electro-induction) analysis of printed circuit boards with multilayer topology is proposed. It is shown that reverse engineering allows not only to repeat the design in the form of a modification, but also completely to completely recreate the whole technological production cycle for the sample under study.